BILATERAL TORTUOUS INTERNAL CAROTID ARTERIES - a case report, otorhinolaryngologic and general clinical implications - Klaudia Ziółkowska; Chavdar Bachvarov; Nikolay Sapundzhiev; Petia Genova (Peytchinski Publishing, 2017)
Variations in the anatomical course of the cervical portion of the internal carotid arteries appear to be more common than expected and recognised, reaching a prevalence of 10-43%. A case of atypical course of both internal carotid arteries with medial transposition is described. The general clinical implications are presented in the base of review the literature. In an otherwise healthy adult female pulsating masses on the posterior oropharyngeal wall were observed on transnasal endoscopy for other indications. Contrast enhanced computer tomography revealed bilateral symmetrical tortuous internal carotids, angulated medially at the level of C2 and almost contacting in the midline. However, no significant stenosis was ascertained within any of the evaluated arteries. The patient was informed about potential risk during the prospective surgical procedures around the pharyngeal area. Carotid tortuosity may present a potential threat in otolaryngological surgery. Whereas no symptoms occur in the most of the patients and the condition can be an accidental finding during physical examination as well as endoscopic or radiological evaluation, the frequency in the general population is higher than assumed. The treatment is not indispensable, however, setting down in the patient's medical history is important. Medical specialists should keep in mind that aberrant internal carotid arteries pose a risk of severe haemorrhage when even routine surgical or diagnostic procedures within the head and neck region are performed.